2015
DOI: 10.1590/s0036-46652015000400004
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION OF Cryptococcus neoformans FROM ENVIRONMENTAL SAMPLES COLLECTED IN SOUTHEASTERN NIGERIA

Abstract: SUMMARYCryptococcosis caused by Cryptococcus neoformans is the second most common fungal opportunistic pathogen and a lifethreatening infection with serious clinical manifestations especially in HIV/AIDS and other immunocompromised patients. In Nigeria, HIV/AIDS infection has reached an alarming level. Despite this, information on the presence of this fungus in clinical and environmental samples is very scanty in Nigeria and many other parts of Africa. We set out to evaluate the presence of Cryptococcus neofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
3
13
0
3
Order By: Relevance
“…This result confirms the presence of this yeast in the environment, in the west region of Cameroon. Similar studies carried out in Nigeria and Jordan showed prevalences of 22.0% (39/177) and 33.3% (336/1009) respectively (16,17). However, in the above studies, the authors used only pigeon dropping and materials under canopies of eucalyptus trees for isolation, not bat guanos.…”
Section: Discussionsupporting
confidence: 76%
“…This result confirms the presence of this yeast in the environment, in the west region of Cameroon. Similar studies carried out in Nigeria and Jordan showed prevalences of 22.0% (39/177) and 33.3% (336/1009) respectively (16,17). However, in the above studies, the authors used only pigeon dropping and materials under canopies of eucalyptus trees for isolation, not bat guanos.…”
Section: Discussionsupporting
confidence: 76%
“…The overall isolation rate (22.0%) obtained in this study was higher compared to the single report from Awka and Jos who reported isolation rates of 14.4% and 13%, respectively. 89,95 Though, Awka was part of the study location in the study by Nweze et al, 38 the isolation rate (14.2%) obtained by Mbata 95 was still lower than the overall prevalence of 22.0%reported by Nweze et al 38 It is important to note that these studies are about 13 years apart.…”
Section: Cryptococcus and Cryptococcosis In Nigeriamentioning
confidence: 86%
“…24 the prevalence of CM in the population was 2.6% with 33% mortality. 30 Then there were increased meningitis cases in HIV patients in Abidjan; hence, Ouattara et al 31 38 Kenya-10%, 39,40 Tunisia-10.4%, 34 Egypt-18% 41 and Libya-34%. 42 The clinical strains isolated were C neoformans (A, AFLP1/VNI), C neoformans × Cryptococcus deneoformans hybrids (AD, AFLP3/VNIII) and Cryptococcus deuterogattii (B, AFLP6/VGII) the only genotype found so far in Africa.…”
Section: Cryptococcus and Cryptococcosis In The Republic Of Beninmentioning
confidence: 98%
“…Following the successful crossing of the blood-brain barrier (BBB), the fungal cells hinder the brain's ability to reabsorb cerebrospinal fluid (CSF), consequently causing an inflammatory condition called meningoencephalitis [19]. This condition is often fatal in immunocompromised cases and is also regarded as an acquired immunodeficiency syndrome (AIDS)-defining illness [20]. Thus, it is not surprising to document high mortality rates due to CNS cryptococcal infection among people infected with HIV [21].…”
Section: Introductionmentioning
confidence: 99%